2017
DOI: 10.1038/srep44497
|View full text |Cite
|
Sign up to set email alerts
|

Glycol porphyrin derivatives and temoporfin elicit resistance to photodynamic therapy by different mechanisms

Abstract: The development of drug resistance is a major problem which often occurs during anticancer chemotherapies. Photodynamic therapy (PDT) has been studied as an alternative treatment modality for drug-resistant tumors, however the question of resistance to PDT and potential cross-resistance with chemotherapy has yet to be fully answered. To investigate the mechanism of resistance to PDT, we developed an in vitro experimental model system in a mouse mammary carcinoma cell line 4T1. We used two ethylene glycol deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
(69 reference statements)
2
22
0
Order By: Relevance
“…This could point to a larger cancer stem cell component in the resistant populations 47 ; although this should be confirmed. Similar results were obtained with the squamous cell carcinoma SCC-13 17 , 48 and the mammary carcinoma 4T1 49 . Regarding to the type of tumours developed, no relevant histological differences were observed, except for the presence of osteoid tissue in the tumours generated from BSZ P, CSZ P and CSZ 10 th G. These histological features presented similarities to one uncommon human BCC subtype, the basal cell carcinosarcoma, very rare in patients and with an equivalent metastasis capacity to conventional BCCs.…”
Section: Discussionsupporting
confidence: 86%
“…This could point to a larger cancer stem cell component in the resistant populations 47 ; although this should be confirmed. Similar results were obtained with the squamous cell carcinoma SCC-13 17 , 48 and the mammary carcinoma 4T1 49 . Regarding to the type of tumours developed, no relevant histological differences were observed, except for the presence of osteoid tissue in the tumours generated from BSZ P, CSZ P and CSZ 10 th G. These histological features presented similarities to one uncommon human BCC subtype, the basal cell carcinosarcoma, very rare in patients and with an equivalent metastasis capacity to conventional BCCs.…”
Section: Discussionsupporting
confidence: 86%
“…Some reports found that retinoid acid binding receptor inhibited cancer cell apoptosis by regulating miR-22/NUR77 axis (21,22). Interestingly, from the results of KEGG pathway enrichment analysis, we found that the genes mainly enriched in molecular metabolism, being consistent with BP of GO enrichment, and the drug, retinoid and porphyrin metabolism are proved involving in irregulated tumor cell metabolism, and resulted in chemotherapy resistant (23).…”
Section: Discussionsupporting
confidence: 64%
“…This recurrence could be associated with cell resistance to PDT, however there are no reports on resistance to this therapy as there is in radiation therapy or chemotherapy in the treatment of other cancers [21]. Despite this lack of information, several studies have tried to clarify the mechanisms involved in PDT resistance, mainly using cancer cell lines [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%